Structural analysis of the northern Nagssugtoqidian orogen, West Greenland:An example of complex tectonic patterns in reworked high-grade metamorphic terrains - Mazur, Stanislaw; Piazolo, Sandra; Alsop, G. Ian (2006)
Structural analysis of the deeply eroded northern flank of the Palaeoproterozoic Nagssugtoqidian orogen shows marked regional variations in both the orientation and type of fabrics, as is characteristic of Precambrian high-grade terrains subjected to polyphase deformation. Here we investigate the relationship between strain, metamorphic grade, and the resulting structural patterns. The study area south of Aasiaat in West Greenland consists of amphibolite-to granulite-grade Archaean orthogneisses and relatively thin supracrustal units. The regional foliation displays a WSW-ENE to SW-NE strike associated with steep to moderate dips towards the WNW or SSE. Lineation trends are WSW-ENE and generally plunge gently towards the WSW. Mesoscopic fold hinges are usually colinear with the regional lineation. A systematic change in the plunge of lineations occurs across the south-western part of the study area. Towards the south, the lineation plunge progressively increases, despite the generally uniform strike of foliation. This southward increase of lineation pitch is typically associated with the transition from L > S or L = S shape fabrics in rocks characterised by a low pitch, to S > L or S fabrics in the zone of moderate to high pitch. The structural patterns point to subdivision of the study area into a southern domain mostly characterised by S or S > L shape fabrics and a moderate to high angle of lineation pitch, and a northern domain showing L > S or L = S fabrics and low angles of lineation pitch. This subdivision corresponds well with the map scale boundary between granulite facies rocks in the south and amphibolite facies rocks farther north. The observed structural pattern may be explained by two alternative tectonic models: (1) northward indentation of the previously cooled granulite block into the rheologically weaker amphibolite domain, and (2) strain partitioning within a mid-crustal transpression zone. In model 2 the northern domain represents a localised zone dominated by strike-slip ...